Communicating Subjective Evaluations - Matthias Lang (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Should principals explain and justify their evaluations? Suppose the principal s evaluation is private information, but she can provide justification by sending a costly unverifiable message. If she does not provide justification, her message space is restricted, but the message is costless. I show that the principal justifies her evaluation to the agent if the evaluation indicates bad performance. The justification assures the agent that the principal has not distorted the evaluation downwards. In equilibrium, the wage increases in the agent s performance, when the principal justifies her evaluation. For good performance, however, the principal pays a constant high wage without justification.
Keywords: D82; D86; M52; 330